Аналіз методів використання 3d-анімації в кіноіндустрії - Пабат, Д. Д.; Халезев, М. С.; Греков, Д. Ю. (ХНУРЕ, 2024)
Mysterious, funny and tragic stories always captivate the viewer, but it is especially important what kind of tool this story is presented: exclusively text or audio, film or internet quest, visual novel and more. Underappreciated is the genre of interactive video and games with a variety of story choices and their consequences, most modern games concentrate on a linear method of presenting stories, sometimes neglecting the variety of wrong choices.
Keywords: 3D-анімація; кіноіндустрія